Increased liver fat and glycogen stores after consumption of high versus low glycaemic index food: a randomized crossover study - Bawden, Stephen; Stephenson, Mary; Falcone, Yirga; Lingaya, Melanie; Ciampi, Elisabetta; Hunter, Karl; Bligh, Frances; Schirra, Jörg; Taylor, Moira; Morris, Peter; MacDonald, Ian A.; Gowland, Penny A.; et al. (Wiley, 2016)
Aim: To investigate the acute and longer-term effects of low (LGI) versus high glycaemic index (HGI) diets on hepatic fat and glycogen accumulation and related blood measures in healthy volunteers.